The Effect Of Dewaka Banana Ripeness Color Index And Fermentation Time On Fermentation Liquid And Solid Waste In Bioethanol Production - Wiyan Afriyanto Pamungkas (Faculty of Agriculture, Musamus University, 2020)
Dewaka banana is a plant that grows abundantly in Merauke Regency. However, it has not widely used because there is a slightly sour taste when they are ripe. Even though, Dewaka banana has a sugar content that is potential used in bioethanol production. Bananas will convert starch content into sugars (glucose) during the ripening stage. One indicator of determining fruit maturity is by looking at the color index of the fruit skin. In bioethanol production, the fermentation process will produce liquid before purified into ethanol through a distillation process and solid waste. This study aimed to determine the effect of the ripeness color index of Dewaka bananas and the fermentation time on the fermented liquid and solid waste obtained from the fermentation of Dewaka banana fruit substrates with maturity color indexes 3, 5, and 7 at the fermentation time of 24, 30, and 36 hours. The results obtained showed that the best combination was obtained from the maturity color index 7 at a 24-hour fermentation time with the fermented liquid as much as 1.45 liters and solid waste as much as 0.35 kg